CONSTITUTIVE MODEL FOR DENSIFICATION OF SINTERED PREFORMS OF AL-TiB2 DURING HOT UPSETTING (International Journal of Food and Nutritional Sciences, 2022)
The main aim of this paper is to evaluate the effect of the relative density on hot deformation behaviour, model and predict the flow stress of the sintered compacts using constitutive equations. Hot compression behaviour of Aluminium-Titanium Diboride alloy sintered compacts was studied by performing hot deformation test in 50 ton hydraulic machine. For this purpose, Al-5%TiB2 composition has been sintered with different relative densities of 0.80, 0.85 and 0.90 which have been prepared by cold pressing. The compacts were hot compressed at different temperatures of 200oC, 300oC, 400oC and 500oC at different strain rates of 0.12s-1, 0.14s-1, 0.16s-1 and 0.18s-1. The graphs are plotted for deformation temperature and strain rate. Flow stress of the powder compacts was described by Zener-Hollomon parameter in an exponential equation containing relative density, compensated material constants and also the deformation energy of activation. As the deformation temperatures and the strain rate were increased and the density decreased, a decrease within the flow stress level was observed.